Li Ka Shing Library Opening Ceremony (Institutional Knowledge at Singapore Management University, 2006)
Dr Li Ka Shing greeting student recipients of Li Ka Shing scholarships at the opening of SMU's Li Ka Shing Library on 24 February 2006.